A CASE REPORT OF CHRONIC HEPATITIS WITH EFFUSION IN A DOG AND ITS THERAPEUTIC MANAGEMENT - H. Prabhavathy; G. Vijaya Kumar; V. Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was aimed to know the chronic hepatitis with abdominal effusion in a beagle dog and its therapeutic management. A 2.5 year old male beagle was presented to Madras Veterinary College teaching Hospital, madras veterinary college, Chennai with the history of inappetence, abdominal distension for past 10 days and the clinical signs of inappetence, fever and palpablelymph node and congested mucous membrane. On Physical examination, dog showed respiratory distress and dull. Dog was subjected for radiography examination, haematology, biochemistry parameters and ultrasound examination. On first day of examination, dog was treated with Lasix at the dose rate of 3 mg/kg body weight, antibiotics and Tribivet injection. Hematology and biochemical values revealed neutrophilia, elevated alkaline phosphatase, total bilirubin, direct bilirubin, and decreased total protein and albumin. The lateral view radiography of abdomen revealed fluid shadow and ultrasound examination revealed that chronic hepatitis with moderate abdominal effusion. In case of clinical suspicion of hepatitis an ultrasonographic liver scan can be of diagnostic aid and the finding of an altered structure can be indicative of a liver problem. In many cases of chronic hepatitis may not be associated with ultrasound abnormalities but ascites can be easily identified. Dog was treated with antibiotic cefotaxime at the dose rate of 25 mg/Kg body weight and Lasix at the dose rate of 3 mg/Kg body weight with liver supplement of Lysibin which contain silymarin and supplement with Astymin syrup for 3 weeks. The animal was reviewed after three weeks of treatment which was subjected for haeamtology, biochemistry and ultrasound examination which revealed there was improvement in the blood parameters with decreased total protein and normal level of Alkaline phosphatase and bilirubin level and ultrasound examination revealed normal study of abdominal effusion and liver echogenicity and dog had normal appetite and normal vital parameters. In this case hepatitis may be due to any viral etiology like adenovirus that may cause hepatitis with effusion that may be respond to treatment and diuretics and brought normal parameters of vital in dog. Chronic hepatitis with effusion may be further confirmed by Liver biopsy and molecular diagnosis.